PERAN EKUITAS MEREK DAN E-WOM DALAM MENDORONG INTENSI PEMBELIAN PRODUK APPAREL LOKAL - Andreas Omegheus Glissando; Arief Helmi (Universitas Bina Taruna Gorontalo, 2025)
This research aims to analyze and compare the influence of brand equity and e-WOM on the purchase intention of local Indonesian apparel. The transformation of community shopping habits from offline to online has triggered a significant surge in the e-commerce market, which is influenced by the ability of apparel brands to utilize digital marketing strategies and the high digital adoption among consumers. The fierce business competition in the digital era demands that companies understand consumer purchase intention to avoid losing market opportunities. Through this understanding, apparel companies need to comprehend the factors that shape purchase intention. This study uses a quantitative approach with a survey method to collect primary data. Model testing was conducted using the PLS-SEM method. The results show that both brand equity and e-WOM influence on forming purchase intention. Brand equity has a greater influence on purchase intention compared to e-WOM, but the difference in influence between the two is not too far, indicating that e-WOM also plays a very important role. Therefore, marketing strategies combining the strengths of brand equity and e-WOM will be an effective combination in building purchase interest for local Indonesian apparel products.